MAJUNYA PERDAGANGAN DAN EKONOMI CHINA (STUDI KASUS: SPECIAL ECONOMIC ZONE) - Bobbie Shinta Dewi Sudarmadji (Universitas Muhammadiyah Yogyakarta, 2006)
China is the third most populated country after Russia and Canada. The number of population in China in 2000 is approximately 1,26 million and this count will always grow up if there is no program to depress the population gromh. At this time, China is a daunted country and become a chance because of its economic growth. China has a lot of number of cheap commodities compared with those from other country, so that China can compete with other industrial countries like Japan and United State. In politic, China is still governed by PKC and everything about politic is in PKC's hand. It is in contrast with the rule of communist country. China is a scarce case by its separation between politic and capitalistic economic. ln this work, author wants to explain about the background of China from the govem of Mao Zhedong who embrace d isolation system and all of China governmental to Deng Xiaoping, the economic condition went better and became courageous to be opened to the world. Fufihermore, by the policy ofDeng in 1978 to open an area in coast region to attract foreign investors by some amenities. From this background, author wants to analyze about : The Trade and Economic Progress in China (Case Study: Special Economic Zone). The main problem is: what is the role of SEZ to increase China economic growth?. To answer this question, author use the perspective power and infestation theory. In this theory, infestation enables a country to save a part of its GDP, so it can increase the economic growth by inviting foreign investor to invest their capital, even less with some amenities in SEZ. From the theories, author makes hypothesis, that is, SEZ is the tool to dttract foreign investor to invest their capital in China. The conclusion from the hypothesis is, Guandong area at the territory of Pearl River Delta has an important role to increase the economic growth in China, even less with the existence of three region in this tenitory: Shenzhen, Zhuhai, and Dongguan, who make Guandong can give the biggest economic earnings to china. Guandong performed a cooperation with two Special Administration Region, namely Hong Kong and Macau. Flong Kong has a strong business fascination, attracted many entrepreneurs to invest their capital. Macau was a Portugal colony, returned to China at April l3th 1987 and became Special Administration Region at December 20th 1999. Because of the excellence of two Special Administration Regions, Guandong performed cooperation with Hong Kong and Macau. It is expected that this cooperation will increase the number of investor and the economic will groMh in China.